Real‐time thermal states monitoring of absorber tube for parabolic trough solar collector with non‐uniform solar flux - Wang, Xudong; Zhang, Daqian; Zhang, Lihui; Jiang, Chuan (International journal of energy research, 2018)
Summary With the world energy shortage problem becoming increasingly prominent, more and more attentions have been paid to the development of renewable energies. Among these sources, solar energy has received extensive attention with its excellent characteristics. The thermal state affects the safety of the solar heat collection system. In this paper, real‐time monitoring of the input heat flux on the inside wall and the temperature field simultaneously of an absorber tube for parabolic trough solar collector were studied. Based on the measured temperatures on the outside wall, the fuzzy adaptive Kalman filter coupled with weighted recursive least squares algorithm (WRLSA) was employed to monitor the heat states of the absorber tube inversely, in which WRLSA was used to acquire the heat flux while fuzzy adaptive Kalman filter was adopted to monitor the temperature field. The method showed strong robustness to resist the ill‐posedness. Accurate monitoring results also can be acquired when there are random disturbances of the heat transfer condition on the inner wall.